The lived experiences of adult children of cross-dressing fathers: a retrospective account - Reisbig, Allison M. J. (Kansas State University, 2007)
This study was aimed at understanding the retrospective experiences of adults who have fathers who are cross-dressers. This study addressed common concerns that partners of men who cross-dress have regarding the impact of fathers’ cross-dressing on children. Previous research indicated that some women in relationships with men who cross-dress actively chose to not have children due to not knowing what effects their partner’s cross-dressing may have on children. Qualitative data from five interviews conducted with adult children of cross-dressing fathers was utilized. Participants reflected upon the following areas: The individual and relational factors that impacted their reaction to having fathers who are cross-dressers; the meanings they created about their fathers’ being cross-dressers; the perceived impact on their social development; and advice they would give to others that may promote the adjustment process for children who have fathers who cross-dress. This study revealed thick description of the adjustment processes for a sample of adult children of cross-dressing fathers. Specifically, the results revealed that the participants adjusted to having fathers who are cross-dressers relatively easily. The closeness of their relationships, the timing and nature of disclosure, their fathers’ comfort levels with being cross-dressers, and the familial response to the fathers’ cross-dressing were all revealed to play important roles in the participants’ acceptance of and adjustment to their fathers’ being cross-dressers. Overall, the participants identified more positive effects than negative in reference to their relationships with their fathers and their social adjustment. This research can assist clinicians in helping couples facing this issue to make informed decisions about having children and in deciding the timing and the preferred circumstances in which fathers should disclose their cross-dressing to their children.
Keywords: Cross-dressing; Cross-dresser; Transgender; Cross-dressing fathers; Children of cross-dressing fathers; Health Sciences, Human Development (0758); Health Sciences, Mental Health (0347)